Lysosomal potassium channels. (March 2022) - Wu, Yi; Xu, Mengnan; Wang, Pingping; Syeda, Alia Kazim Rizvi; Huang, Peng; Dong, Xian-Ping
Abstract: The lysosome is an important membrane-bound acidic organelle that is regarded as the degradative center as well as multifunctional signaling hub. It digests unwanted macromolecules, damaged organelles, microbes, and other materials derived from endocytosis, autophagy, and phagocytosis. To function properly, the ionic homeostasis and membrane potential of the lysosome are strictly regulated by transporters and ion channels. As the most abundant cation inside the cell, potassium ions ( K + ) are vital for lysosomal membrane potential and lysosomal calcium (Ca 2+ ) signaling. However, our understanding about how lysosomal K + homeostasis is regulated and what are the functions of K + in the lysosome is very limited. Currently, two lysosomal K + channels have been identified: large-conductance Ca 2+ -activated K + channel (BK) and transmembrane Protein 175 (TMEM175). In this review, we summarize recent development in our understanding of K + homeostasis and K + channels in the lysosome. We hope to guide the readers into a more in-depth discussion of lysosomal K + channels in lysosomal physiology and human diseases.